“Diseño e implementación de un sistema nivel biestable y medición caudal para tanques elevados en tiempo real” - Aillon Ganchozo, Rumualdo Rafael (2021)
This project design simulates and builds a bistable level control system for the electromechanical laboratory of the Technical University of Cotopaxi to train students in the industrial field through the development of basic concepts in electronic instrumentation and automatic control. For this purpose, aspects such as regulations, organization, and correct connection of each of the elements that make up the control system are taken into account during the simulation and construction procedures. The didactic plant presented is developed for the control, measurement, and monitoring in real-time of the level and flow of two tanks coupled together. The design is composed of three stages: the information gathering phase and selection of the communication media through the visit to the physical station, the instrumentation and control process, and the visualization and data acquisition procedure. The fundamental components to be used for the liquid level control are float type water level sensor, it also has a DC-12V pump in charge of taking the liquid to the control tank, where it is monitored through an ultrasonic sensor (HC-SR04) placed in the upper part of the tank, additionally, the system has a flow sensor (YF-S201) installed at the outlet for data collection from the measurement of the actuating signal. On the other hand, the drainage system consists of a manual valve located at the rear of the tank, which is responsible for making disturbances to the system and give way to the emptying process. For the functions of control, measurement and monitoring will be used as Arduino Mega controller and will be able to develop in two ways. The first one is through a control panel (Display, keyboard, buttons, indicators, etc.) and the second one through a graphical interface developed in LabVIEW 2020. These two ways give the user the possibility to interact in real-time with the prototype, showing changes and characteristics presented in the parameters of each of the input and output variables of the system.